2017
DOI: 10.1093/mnras/stx357
|View full text |Cite
|
Sign up to set email alerts
|

The weak Fe fluorescence line and long-term X-ray evolution of the Compton-thick active galactic nucleus in NGC 7674

Abstract: We present NuSTAR X-ray observations of the active galactic nucleus (AGN) in NGC 7674. The source shows a flat X-ray spectrum, suggesting that it is obscured by Compton-thick gas columns. Based upon long-term flux dimming, previous work suggested the alternate possibility that the source is a recently switched-off AGN with the observed X-rays being the lagged echo from the torus. Our high-quality data show the source to be reflection-dominated in hard X-rays, but with a relatively weak neutral Fe Kα emission l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 112 publications
(165 reference statements)
1
25
2
Order By: Relevance
“…Although strong Fe Kα lines are commonly detected in local bonafide Compton-thick AGNs, for some Compton-thick AGNs, the Fe Kα line might be weak because of ahigh ionization state or alow elemental abundance. For example, NGC7674, which is identified as Compton-thick by NuSTAR, has a weak neutral Fe Kα line of EW≈0.4keV (Gandhi et al 2017), likely because of its high bolometric luminosity (high ionization state). Our 22 Compton-thick sources have highredshifts, 20 of them with z 0.7 > and 6 with z 2 > .…”
Section: Distribution Of N H Excluding Compton-thick Sourcesmentioning
confidence: 99%
“…Although strong Fe Kα lines are commonly detected in local bonafide Compton-thick AGNs, for some Compton-thick AGNs, the Fe Kα line might be weak because of ahigh ionization state or alow elemental abundance. For example, NGC7674, which is identified as Compton-thick by NuSTAR, has a weak neutral Fe Kα line of EW≈0.4keV (Gandhi et al 2017), likely because of its high bolometric luminosity (high ionization state). Our 22 Compton-thick sources have highredshifts, 20 of them with z 0.7 > and 6 with z 2 > .…”
Section: Distribution Of N H Excluding Compton-thick Sourcesmentioning
confidence: 99%
“…The observed X-ray-to-MIR luminosity ratio of a source can therefore give an independent, albeit indirect, assessment of the degree of obscuration (e.g., see Alexander 2017, for a recent review); the observed X-ray luminosity for any significantly absorbed AGN will be suppressed with respect to the intrinsic luminosity, causing it to deviate from the X-ray-to-MIR luminosity relation. This diagnostic has been utilized for other NuSTAR studies of obscured AGNs (e.g., Baloković et al 2014;Lansbury et al 2014Lansbury et al , 2015Stern et al 2014;Annuar et al 2015Annuar et al , 2017Gandhi et al 2017;LaMassa et al 2016). Figure 6 shows the observed X-ray versus intrinsic 6μm luminosities for the eight extreme NuSTAR serendipitous survey sources.…”
Section: Indirect Absorption Diagnosticsmentioning
confidence: 99%
“…Flat G eff values (e.g., 0.5) give empirical evidence for high or CT absorption. Further empirical evidence for CT absorption can be obtained from the detection of a strong fluorescent FeKα emission line at »6.4 keV (with an equivalent width of > a EW 1k e V Fe K , although lower values do not necessarily rule out CT absorption; e.g., Della Ceca et al 2008;Gandhi et al 2017). This reflection feature becomes more prominent with increasing levels of absorption (e.g., Risaliti 2002).…”
mentioning
confidence: 99%
“…Due to the low counting statistics of the spectra, the iron emission line could not be constrained, as its EW resulted in a limit of EW<0.7 keV. This is not necessarily in contrast with the presence of CT absorption, as some CT AGNs have been reported to have unusually weak Fe lines (e.g., Gandhi et al 2017). To allow for the spectral complexity expected for these heavily obscured sources, we used the TORUS model, with an inclination angle fixed at 80 ; filled symbols) sources.…”
Section: Ct Agns In the Nustar Surveymentioning
confidence: 99%